Efektivitas Pelaksanaan Program Tanggung Jawab Sosial Perusahaan PT. Riau Andalan Pulp And Paper di Desa Rantau Panjang Kecamatan Koto Gasib Kabupaten Siak - Norawaty Sihombing (Welfare StatE, 2012)
PT. Riau Andalan Pulp And Paper is a company engaged in the field of pulp and paper industry. As the largest international scale PT. Riau Andalan Pulp And Paper has implemented corporate social responsibility program under a special department with community empowerment as the target. This study aimed to determine whether the implementation of corporate social responsibility programs PT.Riau Andalan Pulp And Paper in the village Rantau Panjang Koto Gasib Siak District effective or not. Based on the analysis of data obtained from six indicators of the effectiveness of corporate social responsibility, namely: understanding the program, targeting accuracy, timeliness, achievement of targets, the achievement of objectives and real change, it is concluded that the implementation of corporate social responsibility programs are effective with total percentage of 61.71%. After joining and became a partner in corporate social responsibility program PT. Riau Andalan Pulp And Paper, the majority of respondents find jobs and additional income, long hours of work increase and a change thought patterns in order to improve the welfare of the family. The data supported the effectiveness of the implementation of corporate social responsibility program based on a Likert scale is high where the average score was obtained for 2.54. Keywords: Effectiveness, Corporate Social Responsibility Program